2013
DOI: 10.1039/c3dt51967h
|View full text |Cite
|
Sign up to set email alerts
|

Doping alkaline-earth: a strategy of stabilizing hexagonal GdF3 at room temperature

Abstract: Hexagonal GdF3 is a more efficient phosphor host compared with the traditional orthorhombic form but the hexagonal phase is thermodynamically unstable at room temperature. Herein, we present a strategy to stabilize hexagonal GdF3 by doping with alkaline-earth ions in a mild hydrothermal reaction system. The selection of the dopant, effect of the dopant amount and the mechanism of the phase transition was discussed in detail. The luminescence variation of GdF3:Eu was demonstrated to verify the phase transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…H-atoms on diglyme ligand have been omitted for clarity. Selected bond lengths (Å) and angles ( ): Gd1-O1 2.499 (3), Gd1-O6 2.375 (3), Gd1-O2 2.443 (3), Gd1-O8 2.395(3), Gd1-O4 2.301 (3), Gd1-O9 2.326 (3), O1-Gd1-O2 64.84 (10), O2-Gd1-O4 105.79 (11), O1-Gd1-O3 111.26 (10), O6-Gd1-O8 i 73.17 (12), O1-Gd1-O8 128.77 (11), O1-Gd1-O9 i 153.28 (11), O3-Gd1-O4 76.64 (11), O6-Gd1-O9 i 120.34 (11), O5-Gd1-O6 74.39 (12), O6-Gd1-O1 71.39 (11), O6-Gd1-O4 137.21 (12), O2-Gd1-O5 145.96 (11). Symmetry code (i) Àx + 1, Ày + 1, Àz + 1.…”
Section: (C) Ft-ir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…H-atoms on diglyme ligand have been omitted for clarity. Selected bond lengths (Å) and angles ( ): Gd1-O1 2.499 (3), Gd1-O6 2.375 (3), Gd1-O2 2.443 (3), Gd1-O8 2.395(3), Gd1-O4 2.301 (3), Gd1-O9 2.326 (3), O1-Gd1-O2 64.84 (10), O2-Gd1-O4 105.79 (11), O1-Gd1-O3 111.26 (10), O6-Gd1-O8 i 73.17 (12), O1-Gd1-O8 128.77 (11), O1-Gd1-O9 i 153.28 (11), O3-Gd1-O4 76.64 (11), O6-Gd1-O9 i 120.34 (11), O5-Gd1-O6 74.39 (12), O6-Gd1-O1 71.39 (11), O6-Gd1-O4 137.21 (12), O2-Gd1-O5 145.96 (11). Symmetry code (i) Àx + 1, Ày + 1, Àz + 1.…”
Section: (C) Ft-ir Spectramentioning
confidence: 99%
“…6 Aer Liu et al demonstrated in 2010 the cubic-to-hexagonal phase transition simply by doping NaYF 4 with larger Gd 3+ cation, 7 many reports have appeared describing doping-induced change in the structure and luminescent properties of the metal uride-based nanomaterials. [8][9][10][11][12][13][14][15][16][17] The alkali metal cations, in particular Li + ion, seem to be preferred choice as a dopant because these can easily be accommodated in the host matrices due to their smaller ionic radii. 6 Besides, few articles have also reported doping of either rare-earth metal cation (La 3+ ) or alkaline-earth metal cations (Sr 2+ , Ca 2+ ) 8 in a lanthanide uoride matrix to tailor the local crystal eld around the lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%
“…GdF 3 nanoparticles (NPs) as an important member of the lanthanide fluoride compounds (LnF 3 ) that possess very low phonon frequencies of crystal lattices and high radiative transition rate are regarded as a kind of excellent host materials for upconversion as well as down conversion photoluminescence [1][2][3][4] . Additionally, GdF 3 can also act as a highly efficient host lattice that achieves multicolor luminescence by varying the dopants since the gadolinium ion (Gd 3+ ) is a good intermediate that migrates and transfers energy [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Among them, uoride materials have drawn much attention due to their unique optical and electronic properties, such as low-energy phonons, high ionicity, electron-acceptor behavior, high resistivity and anionic conductivity. For example, the fabrication of metal uoride nanomaterials, such as CaF 2 nanocubes, 7 SrF 2 nanospheres, 8 BaF 2 nanocubes 9 or nanorods, 10 and hexagonal GdF 3 plates with holes in the center, 11 has been reported for their application in UV lithography, UV-transparent optical lenses, surface conditioning of glass, and upconversion luminescence. However, compared with above mentioned binary lanthanide uorides (LnF 3 , Ln ¼ lanthanide elements), ternary ALnF 4 or Ln 1Ày M y F 3Ày (A ¼ alkali metals, Ln ¼ lanthanide elements, M ¼ Ca, Sr, Ba, Cd) uorides are rarely studied.…”
Section: Introductionmentioning
confidence: 99%